2021
DOI: 10.1210/jendso/bvab022
|View full text |Cite
|
Sign up to set email alerts
|

New Cutoffs for the Biochemical Diagnosis of Adrenal Insufficiency after ACTH Stimulation using Specific Cortisol Assays

Abstract: Context The normal cortisol response 30 or 60 min after cosyntropin (ACTH[1-24]) is considered ≥18 μg/dL (500 nmol/L). This threshold is based on older serum cortisol assays. Specific monoclonal antibody immunoassays or LC-MS/MS may have lower thresholds for a normal response. Objective To calculate serum cortisol cutoff values for ACTH stimulation testing with newer specific cortisol assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 38 publications
4
77
0
1
Order By: Relevance
“…This resulted in a Deming regression with slope of 0.816 (0.768-0.864) and intercept of −0.208 (−0.965 to 0.550) with a correlation coefficient of 0.9846 and a standard error estimate of 1.253. Using this equation, a cutoff of 18 µg/dL with the Roche Cortisol I assay would equal 14.5 µg/dL on the Roche Cortisol II assay, supporting the findings of Javorsky et al [ 1 ].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This resulted in a Deming regression with slope of 0.816 (0.768-0.864) and intercept of −0.208 (−0.965 to 0.550) with a correlation coefficient of 0.9846 and a standard error estimate of 1.253. Using this equation, a cutoff of 18 µg/dL with the Roche Cortisol I assay would equal 14.5 µg/dL on the Roche Cortisol II assay, supporting the findings of Javorsky et al [ 1 ].…”
supporting
confidence: 82%
“…In a recent paper by Javorsky et al [ 1 ], new cortisol cutoffs for cosyntropin stimulation testing to diagnose adrenal insufficiency were proposed for 2 immunoassays as well as a liquid chromatography–tandem mass spectrometry (LC-MS/MS) method. The new cutoffs varied from 14 to 15 µg/dL and were based on comparisons of 110 subjects using the Elecsys Cortisol I assay with a cutoff of 18 µg/dL as the standard.…”
mentioning
confidence: 99%
“…This would potentially reduce overdiagnosis of AI. Additionally, a baseline cortisol less than 55 nmol/L successfully predicted abnormal response to stimulation test (56). A recent retrospective study conducted on 370 patients in Spain (58), confirmed need for sex-specific and assay-specific cutoff values when interpreting corticotropin test to reduce false positives and increase specificity.…”
Section: Establishing the Diagnosismentioning
confidence: 85%
“…Diagnostic cutoff values of serum cortisol depend on the assay used: in most immunoassays, 500 nmol/L is often used as the cutoff to establish diagnosis (6). However, newer monoclonal immunoassays such as the Elecsys ® Cortisol II from (56,57). This would potentially reduce overdiagnosis of AI.…”
Section: Establishing the Diagnosismentioning
confidence: 99%
“…As pointed out by Drs. Jialal and Sood, the cosyntropin-stimulated cortisol cutoffs we provided in our report for the Beckman Access cortisol immunoassay are still valid [ 1 ].…”
mentioning
confidence: 99%